2013
DOI: 10.1371/journal.pone.0068196
|View full text |Cite
|
Sign up to set email alerts
|

Fully Bayesian Inference for Structural MRI: Application to Segmentation and Statistical Analysis of T2-Hypointensities

Abstract: Aiming at iron-related T2-hypointensity, which is related to normal aging and neurodegenerative processes, we here present two practicable approaches, based on Bayesian inference, for preprocessing and statistical analysis of a complex set of structural MRI data. In particular, Markov Chain Monte Carlo methods were used to simulate posterior distributions. First, we rendered a segmentation algorithm that uses outlier detection based on model checking techniques within a Bayesian mixture model. Second, we rende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In some regions where our effect map reaches local maxima holes can be seen in the corresponding maps obtained by SPM. This was reported previously within different data situations (Schmidt et al, 2013). Examples for this are indicated by red circles in the plot.…”
Section: Voxel-based Morphometrysupporting
confidence: 83%
See 1 more Smart Citation
“…In some regions where our effect map reaches local maxima holes can be seen in the corresponding maps obtained by SPM. This was reported previously within different data situations (Schmidt et al, 2013). Examples for this are indicated by red circles in the plot.…”
Section: Voxel-based Morphometrysupporting
confidence: 83%
“…Although Bayesian versions exist that eliminate the necessity for post hoc correction (Friston and Penny, 2003), spatial information is only considered by smoothing the images with a predetermined smoothing parameter, therefore leading to modification of the original data. As with the previous application it would be favorable to include spatial information in the modeling step, especially as it has been shown that this leads to an increase of the signal to noise ratio (Penny et al, 2005) and statistical power (Schmidt et al, 2013). In this application we show that our MCMC approach is able to provide such a solution by fitting a model with millions of parameters with moderate requirements on computational equipment.…”
Section: Estimation Of a Smooth Lesion Probability Mapmentioning
confidence: 69%
“…The quantitative ICC in reliability testing [56,58,65,66] and uncertainty analysis by Bayesian inference based on the posterior probability distribution [20,[67][68][69] are used for precise interpretation of MRI data and prediction of dynamic structural/functional model analysis. In the present study, the variance among healthy subjects, i.e., within-subject variability and the between-subject variability, had been assessed by the reliability testing through estimation of the ICC with 95 % confidence intervals using one-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerically, the latest available MRI measurement was subtracted by the earliest available MRI measurement, divided by the time in between the scans. Lesion Segmentation Toolbox 2.0.15 23 for SPM12 was used to perform cross-sectional and longitudinal T2 lesion volume segmentations based on the FLAIR volumes. The volumes of contrast-enhancing lesions were manually segmented on the post-contrast 3D T1-weighted images using ITK-SNAP 24 .…”
Section: Methodsmentioning
confidence: 99%